ANALISIS POTENSI PENERIMAAN DAN EFEKTIVITAS PAJAK PENERANGAN JALAN DI KABUPATEN GRESIK - SRI PURWASIH, TYAS Sri (Jurnal Akuntansi AKUNESA, 2014)
This study aims to analyze the potential acceptance and the effectiveness of the existing street lighting tax in Gresik for five years, it is from 2009 to 2013. The data used is from the Department of Revenue, Finance and Asset Management as well as data from the PT. PLN Persero APJ in Gresik. The analytical method used is that the analysis of the calculation of the potential revenues which are calculated based on the tax base and tax rates street lighting as well as to calculate the effectiveness of street lighting tax is calculated based on the realization of the potential tax revenue and street lighting. The results of this study indicate that the potential for street lighting tax revenues in Gresik, calculated from all total potential street lighting tax revenues based on group rates for five years is that Rp. 206.024.635.291 and for the effectiveness of street lighting tax results in Gresik is considered as effective.Keywords:Street lighting tax base, Potential Revenue, Tax Revenues streetlighting, and Effectiveness.